Lignin-based controlled-release urea improves choy sum growth by regulating soil nitrogen nutrients and bacterial diversity - Chen, Xiaojuan; Lu, Bosi; Lv, Bowen; Sun, Shaolong (Frontiers in Plant Science, 2024)
Lignin, as one of the few renewable resources among aromatic compounds, exhibits significant potential for applications in the agricultural sector. Nonetheless, there has been relatively limited research on the effects of lignin-based controlled-release urea (LCRU) on soil nitrogen nutrition and bacterial diversity. In this paper, the impact of LCRU on the growth of choy sum was investigated through a two-season field experiment. The findings suggest that the plant height, stem diameter, SPAD value, and above-ground dry weight under LCRU application surpassed those with conventional urea (CU), increasing by 40.27%, 26.97%, 52.02%, and 38.62%, respectively. Furthermore, the condition that the urea content was reduced by 15% (LCRU15) caused improvements of 24.76%, 26.97%, 43.23%, and 30.86% in the respective variables. Additionally, compared with the CU, the contents of vitamin C, soluble sugar, and soluble protein in choy sum were increased by the LCRU and LCRU15 treatments, and yet no significant differences were observed between the LCRU and LCRU15 treatments. Notably, the nitrogen used efficiency of choy sum increased to 68.90% with the LCRU15 treatment, compared to 64.29% with the LCRU treatment. The levels of soil available nitrogen, NO3 --N, and NH4 + -N were augmented by the LCRU and LCRU15 treatments. Meanwhile, soil urease and nitrate reductase activities were increased by 22.4%-28.6% and 12.3%-14.5%, respectively. Moreover, soil high-throughput sequencing results illustrated that the LCRU15 treatment enhanced the diversity and abundance of bacteria, particularly the abundance of Actinobacteria, Firmicutes, and Cyanobacteria, which can accelerate the decomposition of organic matter. In short, LCRU improves choy sum yield by influencing soil properties, enzyme activity, and microbial communities. These findings are anticipated to offer practical value for the sustainable application of LCRU in agriculture.